Comparison of the Effects of Target-Controlled Infusion of Propofol and Sevoflurane as Maintenance of Anesthesia on Hemodynamic Profile in Kidney Transplantation - Dita Aditianingsih; Besthadi Sukmono; Tjues A. Agung; Willy Y. Kartolo; Erika S. Adiwongso; Chaidir A. Mochtar (Anesthesiology Research and Practice)
Background. Target-controlled infusion (TCI) propofol and sevoflurane are common agents for general anesthesia, including for kidney transplantation procedure. This study compared the effect of TCI propofol and sevoflurane on intraoperative hemodynamic profile in kidney transplant patients. Methods. A single-blinded prospective study was performed in 46 kidney transplant recipients who were randomized into receiving TCI propofol or sevoflurane as anesthetics maintenance. Hemodynamic parameters such as mean arterial pressure (MAP), cardiac index (CI), stroke volume index (SVI), and systemic vascular resistance index (SVRI) were measured at baseline before induction, postintubation, first surgical incision, every 15 minutes after the first incision, reperfusion, and 15 minutes after reperfusion. Data were analyzed using unpaired t-test, paired t-test, and general linear model. Results. Intraoperative MAP, CI, SVI, and SVRI changes were similar in both groups (p = 0.480, 0.216, 0.086, and 0.054). In comparison to the baseline value, TCI propofol and sevoflurane groups showed significant reductions of MAP at postintubation (p=0.010; p<0.001) and during the first surgical incision (p=0.009; p<0.001); significant reduction of CI at postintubation (p=0.003; p<0.001) and during the first surgical incision (p<0.001; p<0.001); significant reduction of SVI at postintubation (p=0.013; p=0.008), during the first surgical incision (p=0.008; p=0.003), and 15 minutes after reperfusion (p=0.010; p=0.005); and significant increasing of SVRI during the first surgical incision (p=0.007; p=0.005). The TCI propofol group showed significantly lower SVRI compared to the sevoflurane group postintubation (p=0.029) and during the first surgical incision (p=0.026). Conclusion. Intraoperative hemodynamic profile was similar between the TCI propofol and sevoflurane group during kidney transplant surgery. The TCI propofol group had higher CI and SVI but showed significantly lower SVRI as compared to the sevoflurane group. The incidence of postanesthesia agitation, postoperative outcome, and complication were not significantly different between the two groups.